Developing a groundwater conservation area using analytical hierarchy process in Randublatung groundwater basin. Issue 1 (November 2021) - Hartono, A; Hendrayana, H; Akmaluddin,
Abstract: Randublatung Groundwater Basin is a cross-regional Groundwater Basin located in Central Java with an area of 203 Km 2 . The increase of population in this area led to the increasing need for groundwater not only for freshwater sources and consumption but also for agriculture and industrial needs. The rise of uncontrolled groundwater usage can result in pollution and degradation in the quality and quantity of groundwater. There need to be conservation efforts to maintain the sustainability of groundwater utilization. This study aims to determine conservation zones and management priorities in the Randublatung groundwater basin area. Conservation zones are determined based on the value of their parameters: (a) availability and potential of groundwater, (b) groundwater depletion, (c) changes in groundwater quality, (d) land use, (e) aquifer characteristics, (f) prioritization of groundwater protection areas, and (g) water use. Those parameters are weighed using the Analytic Hierarchy Process (AHP) method and then overlaid corresponding to the weight of the parameter to acquire the matrix of conservation zones. The results indicate the type of lithology in the research area was an alluvial deposit—the development of the data processing presented in the form of a map of groundwater. There are four types of conservation zones in a confined aquifer, i.e., secured, vulnerable, and critical.